Expanding the empirical study of virtual reality beyond empathy to compassion, moral reasoning, and moral foundations - Dunivan, Dennis W.; Mann, Paula; Collins, Dale; Wittmer, Dennis P. (Frontiers in Psychology, 2024)
This study utilizes a controlled experimental design to investigate the influence of a virtual reality experience on empathy, compassion, moral reasoning, and moral foundations. With continued debate and mixed results from previous studies attempting to show relationships between virtual reality and empathy, this study takes advantage of the technology for its ability to provide a consistent, repeatable experience, broadening the scope of analysis beyond empathy. A systematic literature review identified the most widely used and validated moral psychology assessments for the constructs, and these assessments were administered before and after the virtual reality experience. The study is comprised of two pre-post experiments with student participants from a university in the U.S. The first experiment investigated change in empathy and moral foundations among 44 participants, and the second investigated change in compassion and moral reasoning among 69 participants. The results showed no significant change in empathy nor compassion, but significant change in moral reasoning from personal interest to post-conventional stages, and significant increase in the Care/harm factor of moral foundations. By testing four of the primary constructs of moral psychology with the most widely used and validated assessments in controlled experiments, this study attempts to advance our understanding of virtual reality and its potential to influence human morality. It also raises questions about our self-reported assessment tools and provides possible new insights for the constructs examined.